TEACHER PERCEPTIONS TOWARD THE IMPLEMENTATION OF DEEP LEARNING APPROACH IN ENGLISH CLASSROOM - Zelta Jufita Alsidah; Asep Hardiyanto (Universitas Muhammadiyah Makassar, 2026)
As a pedagogical approach that promotes meaningful knowledge, critical thinking, and active student participation, deep learning has been more and more advocated within the Merdeka Curriculum. The amount of data available on how junior high school English instructors use and understand deep learning concepts is, however, still limited. The purpose of this research is to find out how the English instructors at SMP Negeri 3 Kotabumi feel about using deep learning in their classrooms. Five English instructors participated in the study, which used a qualitative research methodology to gather data via document analysis, classroom observations, and semi-structured interviews. Data was analysed using methods such as data reduction, data presentation, and conclusion drafting and verification. Previous research has mostly ignored the unique context of junior high school English education under the Merdeka Curriculum, therefore this study fills that gap by examining how teachers perceive and implement deep learning in the classroom. Teachers have a favourable attitude towards deep learning and conceptualise it as a method that emphasises introspective understanding and contextual knowledge rather than rote memorisation, according to the results. Time restrictions, assessment misalignment, students' memorization-oriented tendencies, and a lack of pedagogical direction all contribute to its poor classroom implementation. In order to guarantee the systematic integration of deep learning principles, this study provides contextual empirical insights into the realities of deep learning implementation in English classrooms and emphasises the necessity of sustained professional development, aligned assessment systems, and institutional support.